Human Resource Management in Improving Employee Performance in Laboratory Supplier Companies : (CV. Dwi Mitra Sejahtera) - Aji, Yovan Khrisna; Kusuma, Kumara Adji; Ubaidillah, Hasan (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This research aims to determine human resource management in improving employee performance at a supplier company (CV. Dwi Mitra Sejahtera). The resource persons in this research were Directors, Employees and Customers of CV. Dwi Mitra Sejahtera. The research method in this proposal is qualitative with a case study approach. The data sources used are primary and secondary. Data analysis techniques use data reduction, data display and data verification, and SWOT analysis. The research results show that human resource management at Cv. Dwi Mitra Sejahtera is not running well and needs to be evaluated.